TRANSPORTATION AND QUALITY OF LIFE - Othman, Abdul Ghapar; Hj. Ali, Kausar (PLANNING MALAYSIA, 2020)
Transportation is one of the key indicators used to measure the Quality of Life of people especially those living in the urban area. Many aspects of transportation are very significant as they have the power to directly influence our way of life in search for a better Quality of Life. Many Malaysians depend on private vehicle transportations to cater their daily travel needs which inevitably leads to an over infiltration of vehicles into the urban area. Automobile dependency has always been viewed as a potential threat to Malaysia’s urban areas, as it contributes to the increase in traffic congestion, higher accidents rate, inefficient usage of urban land, environmental pollution, adverse economic impacts, urban sprawling and reduces the overall quality of public transportation. All these negative impacts deteriorate the quality of life of urban dwellers. This chapter will discuss Malaysia's urban transportation in general, focusing on the struggle between private and public transportation usage and the impacts of automobile dependency towards the urban dwellers’ Quality of Life; as well as putting forward possible strategies and measures in an attempt to provide a balanced urban transportation system.